Reactions Related to CAR-T Cell Therapy - Miao, Lele; Zhang, Zhengchao; Ren, Zhijian; Li, Yumin (Frontiers in Immunology, 2021)
The application of chimeric antigen receptor (CAR) T-cell therapy as a tumor immunotherapy has received great interest in recent years. This therapeutic approach has been used to treat hematological malignancies solid tumors. However, it is associated with adverse reactions such as, cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), off-target effects, anaphylaxis, infections associated with CAR-T-cell infusion (CTI), tumor lysis syndrome (TLS), B-cell dysplasia, hemophagocytic lymphohistiocytosis (HLH)/macrophage activation syndrome (MAS) and coagulation disorders. These adverse reactions can be life-threatening, and thus they should be identified early and treated effectively. In this paper, we review the adverse reactions associated with CAR-T cells, the mechanisms driving such adverse reactions, and strategies to subvert them. This review will provide important reference data to guide clinical application of CAR-T cell therapy.